The sequence { a n } is defined by a 0 = 1 , a 1 = 1 , and a n = a n − 1 + a n − 2 a n − 1 2 for n ≥ 2 . The sequence { b n } is defined by b 0 = 1 , b 1 = 3 , and b n = b n − 1 + b n − 2 b n − 1 2 for n ≥ 2 .
Find a 3 2 b 3 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For a-series We can observe the pattern & see that a n = n !
For b-series we have:
b 0 = 0 ! ∗ 1
b 1 = 1 ! ∗ 3
b 2 = 2 ! ∗ 6
b 3 = 3 ! ∗ 1 0
So we have n! x (a level-2 A.P with common difference 2,3,4,.....33)
b 3 2 = 3 2 ! ∗ ( 1 + 2 + 3 + . . . . . 3 3 ) = 3 2 ! ∗ 5 6 1
b 3 2 / a 3 2 = 5 6 1
Problem Loading...
Note Loading...
Set Loading...
Sequence a is very easy easy to figure out and we obtain the general term for sequence a: a n = n !
For series b after calculating b 3 , b 4 the pattern can be observed and it is:
b 3 = 3 × 4 × 5
b 4 = 3 × 4 × 5 × 6
Hence
b n = 3 × 4 × 5 . . . . . . . . . . . . . . ( n + 2 )
Hence a 3 2 b 3 2 :
a 3 2 b 3 2 = 3 2 ! 3 × 4 × 5 . . . . . . . . . . . . . . ( 3 4 )
⇒ 3 3 × 1 7 = 5 6 1